Campylobacter jejuni ssp. jejuni bacteraemia in a patient with BCR-ABL-positive chronic myelogenous leukaemia in remission on dasatinib therapy. Issue 6 (19th December 2015) - Karrasch, Matthias; Pfister, Wolfgang; Edel, Birgit; Stallmach, Andreas; Hagel, Stefan; Hochhaus, Andreas; Rödel, Jürgen
Abstract : Introduction: We report an unusual case of C ampylobacter jejuni bacteraemia in a patient with Philadelphia chromosome-positive, BCR-ABL-positive chronic myelogenous leukaemia in complete cytogenetic and major molecular remission after dasatinib/IFN therapy. Case presentation: On admission, the patient presented with fever and acute haemorrhagic diarrhoea. Initial empiric antibiotics consisted of ceftriaxone and metronidazole. Stool and blood culture samples were collected and submitted for evaluation; these specimens were processed as per laboratory protocol. Several Gram-negative, spiral rods could be identified microscopically in Gram-stained slides from bottled blood and stool cultures. Isolate identification was performed on the Vitek 2 system using a GN identification card and API Campy strips and by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). Discrepant identification was obtained between the Vitek versus the API Campy test and MALDI-TOF. Erythromycin susceptibility testing was done using an Etest, whereas all other susceptibility testing and breakpoint analysis was done following the EUCAST procedure. Initial empiric antibiotic treatment was switched from ceftriaxone to ciprofloxacin according to antibiotic susceptibility testing (AST) and Etest (ciprofloxacin MIC of 0.094 μg ml − 1 ) results. C. jejuni bacteraemia was successfully eradicated after 1 week of ciprofloxacin therapy. Conclusion: This case describes the rare event of a Campylobacter bacteraemia, which could have been falsely interpreted because of non-specific colony morphology and the initial Vitek result. Only the combination of microscopy, MALDI-TOF and an API Campy test was able to rapidly identify this bacterium as C. jejuni. This case also shows the importance of immediate AST- and MIC-adapted antibiotic treatment in immunocompromised febrile patients suffering from Campylobacter -induced bloody diarrhoea.